MODELING THE BEHAVIOUR OF A BRIDGE UNDER LOAD OBSERVED THROUGH TOPOGRAPHICAL METHODS - Cornel Arsene (Agricultura)
Bridges are works of art whose exploitation must be carried out under conditions of complete safety. Most of the bridges in this country were built in the past century. As a result, works are needed to obtain information about the degree of stability of the analyzed bridge and to identify the measures that must be adopted to ensure its safe operation. This paper presents aspects regarding the study of the behavior of a road bridge in order to determine the solutions so that it can continue to be used safely.